The Texas job - Wortham, Reavis Z. (Poisoned Pen Press, 2022)
"Texas Ranger Tom Bell is tracking a fugitive killer when he rides into Pine Top, a hastily erected shanty-town crawling with rough and desperate men-oil drillers, come by the thousands in search of work. It soon becomes apparent that the lawman's poking around has irritated the wrong people, and when two failed attempts are made on his life, Bell knows that he's getting closer to finding out who is responsible for cheating and murdering the local landowners in order to access the rich oil fields flowing beneath their farms. When they ambush him for a third time while he's out with a local woman he's fallen for, they make the deadly mistake of killing her and leaving him alive"--